Efektivitas Marketplace Dalam Meningkatkankonsentrasi Pemasaran Dan Penjualan Bagiumkm Di Kota Gunung Sitoli - Zega, Selviaman; Mendrofa, Yufita; Zendrato, Jefriniat Jaya; Halawa, Toberman (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The research conducted by the author aims to investigate and explain how centralized marketing and sales of MSME products are. In an effort to spur the development and growth of small businesses or MSMEs, a certain way or method is needed to increase their sales. One of the efforts made is to utilize digital media which has rapidly developed online application by many business actors. The problem that arises is how to choose and determine the most effective media in order to increase marketing activities so that sales turnover can increase significantly. Marketplace is a platform that provides effective solutions for MSMEs to improve marketing and sales in the current era of modernization, especially in the digital sector. In this research, the author used a survey method among MSMEs in the Gunungsitoli city area who were still actively using the marketplace platform. The benefit of a marketplace is that it is able to expand market reach so that it can increase the number of sales and facilitate transactions between sellers and buyers. Furthermore, using the marketplace certainly has several obstacles; including price competition between fellow MSME players, commission fees. On this occasion, the research carried out was an effort to propose a strategy for MSMEs in the city of Gunungsitoli to make perfect use of the marketplace platform.